A Place at School for Musical Expression: Sensory ethnography in collaboration with adolescents - Batista Pina, Ana Paula (2017)
This paper describes an analysis of the musical experiences of 12-15 year-old adolescents, in a seventh grade public school class, with day-long (integral) education. The field research was organized around three workshops that promoted collective productions of photographs, and sound and video recordings related to the musical experiences of the teenagers. A methodological mosaic was built, based predominantly on sensory ethnography. Interviews that incorporated photo-voice technique were considered as a catalyzing component of the narratives developed. Three categories of analysis were identified: the relationships of adolescents with music; peer culture interfaced with the school culture; and collaborative learning. By promoting these sensory experiences it was possible to understand how the adolescents expressed themselves and related to their peers.